Comparative analysis of small and medium-sized enterprises (SMES) versus large companies during the COVID-19 pandemic: Evidence from Moroccan financial market - Abdellah, Alahyan; Mouncif, HARABIDA; Bouchra, RADI (Edelweiss Applied Science and Technology, 2024)
The COVID-19 pandemic significantly affected global financial markets, and Morocco proved no exception. This article analyzes the impact of the pandemic-related announcement on the stock market returns of small and medium-sized enterprises (SMEs) and large companies listed on the Casablanca Stock Exchange. Using event study methodology. This research reveals that SMEs suffered more significant and prolonged declines in stock market returns than large companies, which demonstrated greater resilience. The results underline the importance of adopting crisis management strategies tailored to the specific characteristics of companies according to their capitalization. This offers insights for decision-makers, investors and managers seeking to navigate through periods of major economic turbulence.